Sheep Feeding Strategies in the Face of Declining Steppe Fodder Resources in Tebessa Region/Algeria - Slimani, Atika; Huguenin, Johann; Bairi, Abdelmadjid; Bensouiah, Riad; Allaoua, Abdelkamel (Annals of Arid Zone, 2022)
In Algeria, sheep farming in the steppe areas is the main source of incomefor the populations of these regions. The share of pasture in the daily food ration ofsheep has become very low, less than 30%. As a result, breeders have diversified theirfeeding system strategies. Our questioning concerns the different strategies adoptedby breeders and their efficiency to deal with the lack of fodder from natural stepperangelands. To carry out our research, we used free interviews, with resource persons(extension worker, developer, etc.) and surveys/interviews with 100 breeders fromtwo municipalities in the center of the province of Tébessa. We opted for a holisticand systemic approach to acquire and analyze our collected information. This result inthree main feeding strategies adopted by 3 groups of herders: The 1st strategy exploitedall the food resources available in the study environment, namely the exploitation ofnatural rangelands, pastures from cropland, fodder supplementation and concentratesupplementation (barley grains and wheat bran, etc.), the 2nd strategy used all theresources of the 1st except natural rangelands. The 3rd strategy consisted of grazing thefree fodder supply from natural rangelands of different statuses and using the cheapestconcentrated feeds (wheat bran). The use of supplementation in concentrate was essential,it was found in all strategies.